A PCR-based DNA fingerprinting technique: AFLP for molecular typing of bacteria. - Lin, J J (1996)
Amplified restriction fragment polymorphism (AFLP) is a PCR-based DNA fingerprinting technique. In AFLP analysis, bacterial genomic DNA is digested with restriction enzymes, ligated to adapters, and a subset of DNA fragments are amplified using primers containing 16 adapter defined sequences with one additional arbitrary nucleotide. Polymorphisms of different Escherichia coli strains or Agrobacterium tumefaciens strains were demonstrated as distinct, unique bands in a denaturing sequencing gel using AFLP. The polymorphisms detected between BL21 and BL21F'IQ and between DH5 alpha and DH5 alpha F'IQ strains indicated that AFLP is able to resolve differences in F' episomal DNA (approximately 100 kb).